Harnessing Genomic and Bioinformatic Data to Broaden Understanding of Leukaemia Across Continents - Gumelar, Gugun; Ulfa, Mia Maria; Amukti, Danang Prasetyaning; Irham, Lalu Muhammad; Sapto Yuliani,; Adikusuma, Wirawan; Khairi, Sabiah; Darmawi, Darmawi; Rockie Chong,; Ilker Ates,; Dilpreet Singh,; Aditya Ashok Chavan, (Scripta Medica, 2024)
Background/Aim: Leukaemia is a malignant disease of blood cells found in the bone marrow, which can be divided into acute lymphocytic leukaemia and myelocytic leukaemia. Current management of acute leukaemia still uses chemo therapy as the main therapy but has many side effects, therefore a new approach is needed to identify genetic factors involved in leukaemia. The aim of this study was to investigate gene variations that have potential pathogenic properties in leukaemia.Methods: This study used genome-wide association study (GWAS) data obtained from the National Human Genome Research Institute (NHGRI) to search for genomic variants associated with leukaemia. The data was then screened using SNPnexus to detect potentially protein-damaging variants. Furthermore, the gene expression of these variants was analysed using the GTEx portal. Results: Of the 2115 genomic variants found, four were deleterious, namely rs12140153, rs140386498, rs757110 and rs2066827, representing four different genes, namely PATJ, MINDY1, ABCC8 and CDKN1B. The allele frequency distribution of the variants showed variation between continents, with rs757110 and rs2066827 having different and higher expression than rs12140153 and rs140386498. Gene expression of the variants also varied between tissues, with rs757110 and rs2066827 having higher expression than rs12140153 and rs140386498. Conclusion: This study successfully identified four genomic variants associated with leukaemia and showed differences in gene distribution and expression between populations and tissues. These findings may provide new insights into the molecular mechanisms and risk factors of leukaemia.